FLYPAPER EFFECT PADA DANA ALOKASI UMUM (DAU) DAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP BELANJA DAERAH (BD) DI MALANG RAYA TAHUN 2011-2017 - Junaidi Junaidi; Nur Diana; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThis study aims to find out whether the Flypaper Effect transfer to the GeneralAllocation Fund from the central government and the Regional Original Revenueaffect Regional Expenditures. In this study, there were three populations and thepopulation of this study was the local government in Malang, consisting ofMalang Regency, Malang City, Batu City. Previously Batu City was part ofMalang Regency and became an autonomous city since 2001. So Batu City wasincluded in the sample of this study because Batu City was still listed in the areain Malang Raya. Based on the first hypothesis of the influence of GeneralAllocation Funds and Regional Original Revenues on Regional Expenditures in2011-2017 it can be seen that the amount of DAU and PAD has a positive effecton the amount of Regional Expenditures, meaning that the greater the GeneralAllocation Funds and Original Regional Opinions received by the governmentwill have a large influence the amount of Regional Expenditures.Based on the second hypothesis the influence of General Allocation Funds andRegional Original Revenues on Regional Expenditures partially in 2011-2017can be seen that PAD and DAU Affect Regional Expenditures.Keyword: Regional Original Assets, General Allocation Funds, RegionalExpenditures, Flypaper Effect